Troublemaker - Cho, John 1972-; Suk, Sarah (Little, Brown and Company, 2023)
On the first night of rioting in the wake of the Rodney King verdict, Jordan's father leaves to check on the family store, spurring twelve-year-old Jordan and his friends to embark on a dangerous journey through South Central and Koreatown to come to his aid, encountering the racism within their community as they go
Keywords: Rassismus; Asiaten; Junge -- 12 Jahre; Koreaner; Amerikaner; Los Angeles, Calif.; Families / California / Los Angeles / Juvenile fiction; Korean Americans / Juvenile fiction; Rodney King Riots, Los Angeles, Calif., 1992 / Juvenile fiction; Racism against Asians / Juvenile fiction; Race relations / Juvenile fiction; Los Angeles (Calif.) / History / 20th century / Juvenile fiction; Family life / California / Los Angeles / Fiction; Rodney King Riots, Los Angeles, Calif., 1992 / Fiction; JUVENILE FICTION / General; California / Los Angeles; 1900-1999; Social problem fiction